ANALISIS PENGENDALIAN KUALITAS CAT GUNA MENGURANGI TINGKAT KECACATAN DI PT. PABRIK CAT TUNGGAL DJAJA INDAH - Muchamad Prayogo Utomo; Asmungi Asmungi (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
The company implements a system to monitor the quality of production results in order to obtain product quality standards that are able to challenge business competition locally and outside the region. The company's standardized product defect target is a maximum of 5% of the total production target in 1 month. When the production defect value reaches a defective quality value above 5%, it will tighten the production target and increase the production volume to obtain the desired amount. To overcome this problem, it is necessary to analyze using the Six Sigma Quality Control Method. From this study, the p control map was obtained, it can be seen that the proportion of defects is within the control limits, only in the proportion of December 2022 production control which is above the normal limit of 0.0578 from 0.0571. The most dominant type of defect is paint spots due to dust with 26% of the defect value because it has the highest percentage value with the control chart calculation which is still at the value of the proportion of defects under the control limit. The cause of the high defect rate is due to human negligence, material selection, method use, and machine maintenance